Study of the Fracture Law of Overlying Strata under Water Based on the Flow-Stress-Damage Model. (2nd May 2019) - Wen, Zhijie; Jing, Suolin; Jiang, Yujing; Tian, Lei; Wen, Jinhao; Cao, Zhiguo; Shi, Shaoshuai; Zuo, Yujun
Abstract : To accurately detect the development height of the water flowing fractured zone (WFFZ) in the overlying strata of the working face after mining under water and to ensure the safety and reliability of coal mining, the coal seam located under Weishanhu Lake in the Jisan coal mine was used as the experimental system. A similar laboratory simulation and water injection-based fracturing test system were used with the working face before and after mining activity to calculate, quantitatively detect, and qualitatively analyze the development height of the WFFZ in the overlying strata. Meanwhile, a flow-stress-damage model and its criterion of fracture expansion were established based on the Mohr-Coulomb criterion, and the FLAC 3D software was used to simulate the deformation and failure of the overlying strata and the evolution of WFFZ during the mining process. The results showed that the height ranges of the WFFZ beneath Weishanhu Lake of the Jisan coal mine as established by the above three methods are 30-45 m, 30-48 m, and 30-50 m. In the process of mining, the caving zone and fractured zone are, respectively, subjected to tensile failure and shear failure. The development height of the water flowing through the fractured zone in the overlying strata is basically consistent with the range of the "breaking arch." The flow-stress-damage model and its criterion of fracture expansion can be applied to the fracture law of overlying strata under water under similar geological conditions.